Internalisasi Karakter Disiplin Peserta Didik Melalui Ekstrakurikuler Polisi Taruna (POLTAR) - Aprillio Poppy Belladonna; Neneng Tripuspita; Nikki Tri Sakung (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to examine, analiyze, and understand the application of the character of discipline for students through the role of the cadet police extracurricular. This research use a qualitative approach with a case study method. The location of the research was carried out at SMK Taruna Nusantara Jaya, Cisomang village. The data were obtained through interviews, observations, and documentation studies. The results of the research are as follows: 1) The disciplinary conditions of student have developed better, but there ara still some student who commit disciplinary actions (mild) including being indiscipline when entering school, long hair and not carrying attributes. 2) studens’ views on the police cadet extracurricular that it is a good extracurricular especially in terms of emphasizing discipline, including time discipline and responsibility. 3) the role extracurricukar POLTAR on student discipline is to carry out disciplinary implementation activities including supervising, recording, warning, giving direction, and taking action according to instructions from the coach and student